A non-stoichiometric high-entropy proton conductor electrolyte material, a preparation method and application thereof

CN122576270BActive Publication Date: 2026-10-30INNER MONGOLIA UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611049891.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-10-30
Estimated Expiration
2046-07-15

AI Technical Summary

Technical Problem

该材料通过B位多元素非等摩尔掺杂,以高构型熵稳定立方相,利用局域晶格畸变平坦化质子势能面,降低迁移活化能,同时利用多元素协同效应抑制Ce4+还原,显著提升了低温质子电导率与化学稳定性,克服了现有BZCY基质子导体低温电导率不足、化学稳定性差的缺陷

Benefits of technology

(1)显著提升的离子电导率:本发明通过B位Ce、Zr、Sn、Y、Yb、Sc六种元素的非等摩尔协同掺杂,利用高构型熵稳定立方相,形成的局域晶格畸变平坦化了质子势能面,使质子迁移活化能显著降低。550℃下质子电导率高达0.234S·cm-1。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122576270B_ABST
    Figure CN122576270B_ABST
Patent Text Reader

Abstract

The application discloses a non-equal-molar high-entropy proton conductor electrolyte material and a preparation method and application thereof, and belongs to the technical field of solid oxide fuel cells. 3‑δ Wherein, B sites are occupied by Ce 4+ , Zr 4+ , Sn 4+ , Y 3+ , Yb 3+ and Sc 3+ in non-equal-molar proportions and disorderly. The material is formed by the non-equal-molar proportion solid solution of the six elements in B sites, and a single cubic perovskite phase with high configurational entropy stability is formed. The difference in ion radii of the multiple elements induces local lattice distortion, flattens the proton potential energy surface, and significantly reduces the proton migration activation energy. The proton conductivity of the electrolyte reaches 0.234 S·cm ‑1 at 550 DEG C, the peak power density of the fuel cell based on the electrolyte is 1074 mW·cm ‑2 at 550 DEG C, the fuel cell can still output 67 mW·cm ‑2 at a low temperature of 310 DEG C, and has a long-term stability of more than 135 h.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid oxide fuel cells (SOFCs), and more specifically, to a non-equimolar high-entropy proton conductor electrolyte material, its preparation method, and its application. Background Technology

[0002] Traditional solid oxide fuel cells (SOFCs) operate at excessively high temperatures (typically >800°C), leading to problems such as material aging and high costs. Therefore, the development of low-temperature solid oxide fuel cells (LT-SOFCs) has become a research hotspot. The proton conductor electrolyte, as a core component of SOFCs, directly determines the battery's output power and operational stability. Compared to traditional oxygen-ion conductor SOFCs, proton conductor SOFCs use protons as charge carriers, resulting in lower activation energies and the ability to achieve high power densities in the low-temperature range (300-600°C). This makes it one of the most promising SOFC technologies currently available.

[0003] To balance conductivity and stability, researchers developed BaCeO3-BaZrO3 solid solutions, with BaZr being a typical example. 0.1 Ce 0.7 Y 0.2 O 3-δ (BZCY). This material achieves a balance between high electrical conductivity and chemical stability to some extent, but its low-temperature (<500℃) electrical conductivity is still insufficient, and its long-term operational stability needs to be improved.

[0004] In recent years, high-entropy materials have demonstrated unique advantages in stabilizing crystal structures, suppressing phase separation, and optimizing ion conduction due to the high configurational entropy effect brought about by multi-principal element disordered solid solution. A few studies have applied the high-entropy concept to proton conductor electrolytes, but existing high-entropy proton conductor electrolytes have failed to fully utilize the differentiated synergistic effects of different elements, resulting in insufficient performance at lower temperatures.

[0005] Therefore, developing a high-entropy proton conductor electrolyte material with higher configurational entropy, high electrical conductivity at low temperatures, and excellent chemical stability is of great significance for promoting the development of SOFC at ultra-low temperatures (<350℃). Summary of the Invention

[0006] In view of this, the purpose of this invention is to provide a non-equimolar high-entropy proton conductor electrolyte material, its preparation method, and its applications. This material achieves high configurational entropy by non-equimolar multi-element doping at the B site to stabilize the cubic phase, utilizes localized lattice distortion to flatten the proton potential energy surface, reduces the migration activation energy, and simultaneously utilizes the synergistic effect of multiple elements to suppress Ce. 4+The reduction significantly improves the low-temperature proton conductivity and chemical stability, overcoming the shortcomings of insufficient low-temperature conductivity and poor chemical stability of existing BZCY proton conductors.

[0007] To achieve the objectives of this invention, the following technical solution is adopted: In a first aspect, the present invention provides a non-equimolar high-entropy proton conductor electrolyte material, wherein the chemical formula of the electrolyte material is BaBO. 3-δ In which, position B is determined by Ce 4+ Zr 4+ Sn 4+ Y 3+ Yb 3+ ,Sc 3+ The six elements occupy the space in a non-equimolar ratio in a disordered manner, where δ is the oxygen vacancy content, and 0 ≤ δ < 0.25.

[0008] Among them, non-equimolar ratio means that the mole fraction of each element at the B site is between 5% and 35%, and the mole fraction of each element is not exactly the same.

[0009] Furthermore, the chemical composition of the electrolyte material is BaCe. x Zr y Sn z Y m Yb n Sc w O 3-δ Where x is 0.3~0.35; y is 0.2~0.25; z is 0.1~0.15; m, n and w are all 0.05~0.15; and the sum of x, y, z, m, n and w is 1.

[0010] Furthermore, the chemical composition of the electrolyte material is such as BaCe 0.35 Zr 0.25 Sn 0.15 Y 0.10 Yb 0.10 Sc 0.05 O 3-δ As shown; the electrolyte material has a cubic perovskite structure.

[0011] Furthermore, the tolerance factor t of the electrolyte material is greater than 0.96; and / or the configurational entropy S of the electrolyte material. config A value greater than 1.5R, preferably 1.61R, falls into the high entropy category, where R is the ideal gas constant.

[0012] In this invention, the electrolyte material has a single cubic perovskite structure with space group Pm-3m and tolerance factor t = 0.967, which is close to an ideal cubic structure.

[0013] In this invention, the difference in ionic radii of multiple elements (Ce) 4+ 1.01Å, Zr 4+ : 0.72Å, Sn 4+ : 0.69Å, Y 3+ 0.90Å, Yb 3+ 0.87Å, Sc 3+ The strong local lattice distortion induced by the 0.75 Å light source resulted in a significant broadening of the BO6 octahedral vibrational peak in the Raman spectrum; the proton conductivity of the electrolyte material at 550 °C was not less than 0.23 S·cm. -1 The activation energy for proton migration is reduced to a minimum.

[0014] In a second aspect, the present invention provides a method for preparing the electrolyte material according to any one of the above claims, comprising the following steps: (1) Weigh out the Ba source, Ce source, Zr source, Sn source, Y source, Yb source and Sc source according to the stoichiometric ratio; (2) The weighed raw materials are ball-milled, mixed, and dried to obtain a mixed powder; (3) The mixed powder is pre-calcined at 800~1200℃ for 4~10 h, and then ground to obtain pre-calcined powder; (4) The pre-calcined powder is sintered at a high temperature of 1200~1600℃ for 5~15 h, and then ground to obtain the sintered powder; (5) The sintered powder is ball-milled and dried to obtain electrolyte powder BZCSYYbS.

[0015] Furthermore, in steps (2) and (5), the ball milling speed is 200~300 r / min and the time is 7~9 h; in step (3), the pre-firing temperature is 900℃ and the holding time is 6 h; in step (4), the high-temperature sintering temperature is 1400℃ and the time is 10 h.

[0016] Secondary ball milling can further refine the particles and improve the electrochemical performance of the powder.

[0017] Further, in step (1), the Ba source is selected from BaCO3; the Ce source is selected from CeO2; the Zr source is selected from ZrO2; the Sn source is selected from SnO2; the Y source is selected from Y2O3; the Yb source is selected from Yb2O3; and the Sc source is selected from Sc2O3. Among these, the Ba source is used in excess of 3-8 mol compared to the stoichiometric amount.

[0018] In a third aspect, the present invention provides the application of the electrolyte material described in any of the preceding claims in a solid oxide fuel cell.

[0019] The present invention also provides a solid oxide fuel cell comprising the non-equimolar high-entropy proton conductor electrolyte material described in any of the preceding claims.

[0020] Furthermore, the anode and cathode materials of the solid oxide fuel cell are both Na. 0.15 Li 0.85 Ni 0.80 Co 0.15 Al 0.05 F 0.10 O 1.9-δ , 0≤δ<0.25.

[0021] Furthermore, the Na 0.15 Li 0.85 Ni 0.80 Co 0.15 Al 0.05 F 0.10 O 1.9-δ The preparation methods include: According to the stoichiometric ratio Na:Li:Ni:Co:Al:F = 0.15: 0.85: 0.80: 0.15: 0.05: 0.10, weigh out the following raw materials: LiOH·H2O (≥98.0%, with an additional 5 mol% excess to compensate for lithium volatilization), NaOH (≥96.0%), NiO (Ni content 61%), Co3O4 (≥99.9%), Al2O3 (≥99.99%), and NiF2·4H2O (≥98%). Place the weighed raw materials in a planetary ball mill and ball mill at 200~300 r / min for 4~8 h using anhydrous ethanol as the dispersion medium. After ball milling, dry the slurry at 100~150℃ under a drying lamp until the ethanol has completely volatilized. The dried powder was placed in an alumina crucible and pre-sintered at 500-550℃ for 4-8 hours in air atmosphere, followed by high-temperature sintering at 780-830℃ for 8-12 hours. After furnace cooling, it was ground to obtain Na. 0.15 Li 0.85 Ni 0.80 Co 0.15 Al 0.05 F 0.10 O 1.9-δ Electrode material powder.

[0022] The solid oxide fuel cell of this invention can be assembled using the dry pressing method, with an effective area of ​​0.64 cm². 2 The test was conducted with hydrogen as fuel at the anode and air as oxidant at the cathode within the temperature range of 310-550℃.

[0023] The solid oxide fuel cell of this invention has a peak power density of ≥1074 mW·cm at 550°C. -2 And the output power density at 310°C is ≥67 mW·cm³. -2 And the stable operating time is ≥135 hours.

[0024] Compared with the prior art, the beneficial effects of the present invention are: (1) Significantly improved ionic conductivity: This invention utilizes non-equimolar synergistic doping of six elements (Ce, Zr, Sn, Y, Yb, and Sc) at the B site to stabilize the cubic phase with high configuration entropy. The resulting localized lattice distortion flattens the proton potential energy surface, significantly reducing the proton migration activation energy. The proton conductivity reaches as high as 0.234 S·cm at 550℃. -1 .

[0025] (2) Excellent low-temperature operating performance: Thanks to the significant reduction in activation energy, the fuel cell based on the high-entropy proton conductor electrolyte of this invention achieves a peak power density of up to 1074 mW·cm at 550℃. -2 It can still output 67mW·cm at an ultra-low temperature of 310℃. -2 The power density is higher, while traditional BZCY-based batteries only output 23 mW·cm² at 310°C. -2 (Approximately 3 times improvement). This invention successfully lowers the lower limit of the operating temperature of LT-SOFC to 310°C, breaking through the bottleneck of low-temperature operation.

[0026] (3) Excellent chemical stability: The high entropy effect and the synergistic effect of multiple elements (Zr, Sn) significantly inhibit Ce. 4+ Reduction in a reducing atmosphere (XPS displays Ce) 4+ The proportion is higher than that of BZCY, and it also enhances the chemical stability of the electrolyte in CO2 and water vapor atmospheres, solving the problem of poor stability of traditional BaCeO3-based electrolytes.

[0027] (4) Ultra-long service life: The single cell based on the high-entropy electrolyte of this invention can operate stably for more than 135 hours at 550°C (BZCY only about 12 hours), and the long-term durability is significantly improved. Attached Figure Description

[0028] Figure 1 The XRD patterns of the high-entropy BZCSYYbS electrolyte prepared in Example 1 of this invention are compared with those of the classic BZCY electrolyte. Figure a shows the XRD pattern of the BZCY sample after calcination at 1300-1500℃ for 10 h; Figure b shows the XRD pattern of the BZCSYYbS sample prepared by calcination at the same temperature; Figure c shows a comparison of the XRD patterns of the BZCY and BZCSYYbS samples after calcination at the optimal temperature of 1400℃ for 10 h.

[0029] Figure 2 The Rietveld refined spectra of the high-entropy BZCSYYbS electrolyte prepared in Example 1 of this invention are compared with those of the classic BZCY electrolyte. Figure a shows the refined spectra of the BZCY sample, and Figure b shows the refined spectra of the BZCSYYbS sample.

[0030] Figure 3 A comparison of the Raman spectra of the high-entropy BZCSYYbS electrolyte prepared in Example 1 of this invention with that of the classic BZCY electrolyte.

[0031] Figure 4 The high-entropy BZCSYYbS electrolyte prepared in Example 1 of this invention is compared with the classic BZCY electrolyte using TEM and HR-TEM. Figure a shows the TEM image of the BZCY sample, Figure b shows the HR-TEM image of the BZCY sample, Figure c shows the TEM image of the BZCSYYbS sample, and Figure d shows the HR-TEM image of the BZCSYYbS sample.

[0032] Figure 5 Figure 1 shows the IV / IP curves and long-term stability curves of the fuel cell based on the high-entropy BZCSYYbS electrolyte of Example 2 of this invention. Figure 2a shows the IV / IP curve of the BZCSYYbS sample, and Figure 3b shows the long-term stability curve of the BZCSYYbS sample.

[0033] Figure 6 Based on Example 2 of this invention, the high-entropy BZCSYYbS electrolyte and the classic BZCY electrolyte... EIS curves of fuel cells with electrolytes. Figure a shows the comparison of R0 for BZCY and BZCSYYbS samples at different test temperatures, Figure b shows the EIS curve of the BZCY sample, and Figure c shows the EIS curve of the BZCSYYbS sample.

[0034] Figure 7 This is a comparison of the ionic conductivity and activation energy of the high-entropy BZCSYYbS electrolyte and the classic BZCY electrolyte in Example 3 of the present invention. Figure a shows the ionic conductivity of the BZCY and BZCSYYbS samples, Figure b shows the activation energy of the BZCY sample, and Figure c shows the activation energy of the BZCSYYbS sample.

[0035] Figure 8 This document compares the XPS O1s and Ce3d spectra of the high-entropy BZCSYYbS electrolyte and the classic BZCY electrolyte in Example 3 of this invention. Figure a shows the total XPS spectrum of the BZCY and BZCSYYbS samples; Figure b shows the XPS O1s spectrum of the BZCY and BZCSYYbS samples; Figure c shows the XPS Ce3d spectrum of the BZCY and BZCSYYbS samples; and Figure d compares the oxygen vacancies and Ce valence states of the BZCY and BZCSYYbS samples.

[0036] Figure 9Figure 2 shows the IV / IP curves of the fuel cell based on BaCeO3 electrolyte in Comparative Example 2 of this invention. Figure a shows the IV / IP curve of the BaCeO3 sample, and Figure b shows the long-term stability curve of the BaCeO3 sample.

[0037] Figure 10 Figure 1 shows the IV / IP curves and long-term stability curves of the fuel cell using the classic BZCY electrolyte in Comparative Example 1 of this invention. Figure a shows the IV / IP curve of the BZCY sample, and Figure b shows the long-term stability curve of the BZCY sample. Detailed Implementation

[0038] Although detailed implementation details are provided in the invention application, this does not mean that the invention can only be implemented in these specific ways. The scope of protection of the invention should cover all possible implementation methods, as long as these methods do not depart from the core idea or basic principles of the patent. The purpose of this statement is to convey to those skilled in the art that they can improve or modify the invention based on their own innovation and skills without violating the scope of the invention's claims.

[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.

[0040] Example 1 In this embodiment, the B site is occupied by six elements Ce, Zr, Sn, Y, Yb, and Sc in the following molar percentages: Ce 35%, Zr 25%, Sn 15%, Y 10%, Yb 10%, and Sc 5%. BaCO3 (analytical grade, 99.95%), CeO2 (99.99%), ZrO2 (99.99%), SnO2 (99.99%), Y2O3 (99.95%), Yb2O3 (99.95%), and Sc2O3 (99.95%) are accurately weighed according to stoichiometric ratios. An excess of 5 mol% BaCO3 (based on the theoretical stoichiometric amount) is added to compensate for Ba volatilization loss during high-temperature sintering. The weighed raw materials are placed in a planetary ball mill, using zirconia balls (ball-to-material ratio 5:1) as the grinding medium and anhydrous ethanol as the solvent. After sealing the ball mill jar, the mill is ball-milled at 260 r / min for 8 hours. After ball milling, the powder was dried under a heat lamp at a temperature above 100℃ for 2-3 hours. The mixed powder was placed in an Al2O3 crucible and sintered in a box muffle furnace at 900℃ for 6 hours, then cooled to room temperature with the furnace and ground. The pre-sintered powder was placed in an alumina crucible and sintered in a box muffle furnace at 1400℃ for 10 hours, then cooled to room temperature with the furnace and ground again. The sintered powder was ball-milled a second time at 220 r / min for 6 hours to further refine the particles. After ball milling, the powder was heated under a heat lamp at a temperature above 100℃ for 2 hours to obtain high-entropy BZCSYYbS electrolyte powder.

[0041] Na 0.15 Li 0.85 Ni 0.80 Co 0.15 Al 0.05 F 0.10 O 1.9-δ (Na) 0.15 Li 0.85 NCAF 0.10 Preparation of symmetrical electrodes: According to the stoichiometric ratio Na:Li:Ni:Co:Al:F = 0.15: 0.85: 0.80: 0.15: 0.05: 0.10, the following raw materials were weighed: LiOH·H₂O (≥98.0%, with an additional 5 mol% excess to compensate for lithium volatilization), NaOH (≥96.0%), NiO (Ni content 61%), Co₃O₄ (≥99.9%), Al₂O₃ (≥99.99%), and NiF₂·₄H₂O (≥98%). The weighed raw materials were placed in a planetary ball mill and ball-milled for 6 hours at 260 r / min using anhydrous ethanol as the dispersion medium. After ball milling, the slurry was dried at 120℃ under a drying lamp until the ethanol was completely volatilized. The dried powder was placed in an alumina crucible and pre-sintered at 520°C for 5 hours in air atmosphere, followed by high-temperature sintering at 810°C for 10 hours. After furnace cooling, it was ground to obtain Na. 0.15 Li0.85 NCAF 0.10 O 1.9-δ Electrode material powder. The prepared electrode material was mixed with terpineol at a solid-liquid ratio of 10:3 (g / mL), and an appropriate amount of anhydrous ethanol was added to grind it into a slurry. The slurry was uniformly coated onto a nickel foam mesh (0.64 cm² area). 2 The coating was applied to a substrate and dried at 120°C for 30 min. This process was repeated three times to obtain porous Ni-Na. 0.15 Li 0.85 NCAF 0.10 Symmetrical electrodes.

[0042] The resulting high-entropy BZCSYYbS electrolyte and Na 0.15 Li 0.85 NCAF 0.10 Electrodes were assembled into a single cell using a dry-pressing method: 0.25 g of high-entropy BZCSYYbS electrolyte powder was weighed and placed in a 13 mm diameter stainless steel mold. The Ni-Na electrolyte prepared above was then... 0.15 Li 0.85 NCAF 0.10 Symmetrical electrodes were placed on both sides of the electrolyte sheet, and Ni-Na was formed under a pressure of 400 MPa for 90 s. 0.15 Li 0.85 NCAF 0.10 |BZCSYYbS|Na 0.15 Li 0.85 NCAF 0.10 -Ni sandwich structure (LT-SOFC device), cell diameter 13mm, effective working area 0.64cm² 2 The battery was tested on a self-built fuel cell test platform, with hydrogen gas introduced into the anode (flow rate 130-160 mL / min). -1 Oxygen is introduced into the cathode as an oxidant.

[0043] Prepare a solution using BZCY as the electrolyte and Na using the same method. 0.15 Li 0.85 NCAF 0.10 Electrodes were assembled into a single cell for comparison.

[0044] Figure 1 XRD patterns of BZCY and high-entropy BZCSYYbS samples synthesized by solid-state reaction method after calcination at 1300-1500℃ for 10 h were obtained. Figure 1The XRD patterns of the BZCY samples after calcination at 1300-1500℃ for 10 h are shown in Figure 1. All diffraction peaks are consistent with the BaCeO3 standard card (PDF#75-0431), and no impurity peaks are observed. Furthermore, comparison reveals that the diffraction peak intensity first increases and then decreases with increasing calcination temperature, reaching its maximum at 1400℃, indicating that the material has optimal crystallinity at this temperature. Figure 1 b presents the XRD patterns of BZCSYYbS samples prepared by calcination at the same temperature. At 1300℃, the diffraction peaks are low in intensity, broadened, and contain a few impurity peaks, indicating poor crystallinity of the perovskite structure. When the temperature is increased to 1400℃ and 1500℃, all diffraction peaks are consistent with the BaCeO3 standard card (PDF#75-0431), and no impurity peaks appear, confirming the successful acquisition of the perovskite-structured BZCSYYbS material. Among them, the sample calcined at 1400℃ has the highest diffraction peak intensity and sharpest peak shape, indicating that the phase purity and crystallinity of the material are optimal at this temperature. It is worth noting that compared with the BZCY sample, the diffraction peaks of the high-entropy BZCSYYbS sample are significantly shifted towards higher angles, such as... Figure 1 c. According to Bragg's law, a rightward shift of the peak position means a decrease in the interplanar spacing d, i.e., lattice contraction.

[0045] To quantitatively describe the structural evolution, Rietveld structural refinement was performed on both materials. Figure 2 The corresponding refinement results, tolerance factors, and configuration entropies are summarized in Table 1. The refined lattice parameters, bond lengths, and bond angles reveal the structural evolution from BZCY to BZCSYYbS. The average BO bond length in BZCY is 2.17 Å, while it shortens to 2.14 Å in BZCSYYbS. The bond length shortening is mainly caused by the substitution of smaller cations: Zr 4+ Sn 4+ and Sc 3+ The ionic radii of all of them are smaller than Ce. 4+After these atoms partially occupy the B sites, the average ionic radius at the B sites decreases from 0.84 Å in BZCY to 0.825 Å, leading to a reduction in the equilibrium distance of the BO bonds. Shorter bond lengths are usually accompanied by increased bond energies, which is beneficial for improving the thermodynamic stability of the lattice. The BOB bond angle in BZCY is 170°, while the bond angle in BZCSYYbS increases to nearly 178°. In perovskite structures, the BOB bond angle is a key parameter for measuring the tilt of the BO6 octahedron; the ideal cubic phase has a bond angle of 180°. The bond angle in BZCSYYbS approaches 180°, indicating that the octahedral tilt is significantly suppressed, and the symmetry of the crystal structure is greatly improved. This change is quantitatively described by the Goldschmidt tolerance factor (t). The t value for BZCY is 0.88, while the t value for BZCSYYbS increases to 0.967, very close to the threshold of 1.0 for the ideal cubic structure. The improved tolerance factor is attributed to the synergistic optimization of the ionic radius matching at the B site by multiple elements, thereby releasing the octahedral tilt and causing the crystal structure to tend towards a highly symmetrical cubic phase. Thermodynamically, the configurational entropy of BZCSYYbS reaches 1.61 R, which is typical of the high-entropy range (>1.5 R), providing a thermodynamic driving force for homogeneous solid solution of multiple principal elements. This effectively suppresses phase separation and ensures the formation of a single cubic perovskite phase (no impurity peaks in XRD).

[0046] Table 1. Rietveld refinement data of BZCY and BZCSYYbS after 10 h at the optimal sintering temperature of 1400℃.

[0047] Figure 3 Raman spectra of BZCY and high-entropy BZCSYYbS are shown. 300-500 cm⁻¹ -1 Corresponding to the oxygen octahedral deformation mode, 600-800 cm -1 This reflects the stretching vibration of the BO bond and the structural symmetry. The BO6 peak position of BZCSYYbS is 657 cm⁻¹. -1 Moved to 704cm -1 The bond length shortening observed during XRD refinement confirms the enhanced BO bond energy. Significant broadening of all Raman peaks indicates strong local distortion induced by the multi-principal-element disordered lattice.

[0048] Figure 4 a and c are TEM images of BZCY and BZCSYYbS. Figure 4b and d are the HR-TEM images corresponding to the two samples. FFT transformation was performed on the areas selected by the red box to calculate the interplanar spacings observed in BZCY and BZCSYYbS materials as 0.280 nm and 0.269 nm, respectively, corresponding to the (110) crystal plane. Compared with BZCY, the interplanar spacing of the (110) crystal plane of BZCSYYbS is significantly reduced, further confirming the lattice distortion, which is consistent with the XRD results.

[0049] The performance of the LT-SOFC device prepared above was tested. The test results are as follows: Figure 5 As shown in figure a, using high-entropy BZCSYYbS as the electrolyte and Na 0.15 L 0.85 NCAF 0.10 The fuel cell assembled with symmetrical electrodes achieved a peak power density of 1074 mW·cm³ at 550°C. -2 Meanwhile, at a low temperature of 310℃, it can still achieve 67 mW·cm⁻¹. -2 Power output.

[0050] To further verify the stability of the fuel cell device constructed with the BZCSYYbS composite electrolyte, the battery fabricated in this embodiment was tested under fuel cell operating conditions at 100 mA·cm⁻¹. -2 The results of a long-term stability test of the current density for 135 hours are as follows: Figure 5 As shown in b. The BZCSYYbS electrolyte designed in this embodiment can significantly improve the stability of the battery, with a stability time of over 135 hours, exhibiting good electrochemical stability.

[0051] Figure 6 Its electrochemical impedance characteristics in the temperature range of 310-550℃ were further tested using EIS. Figure 6 This directly compares the ohmic impedance R0 of two battery devices, BZCY and BZCSYYbS, at different temperatures. Figure 6 b and Figure 6 In section c, the EIS data of the two batteries were fitted using the equivalent circuit of R0(R1Q1)(R2Q2). The results show that by implementing a high-entropy doping strategy on the BZCY material, the R0 value of BZCY (550℃, 0.175 Ω·cm) can be improved. 2 ) and polarization impedance R p Value (550℃, 0.195Ω·cm) 2 BZCSYYbS achieved a significantly reduced R0 value (550℃, 0.164 Ω·cm). 2 ) and polarization impedance R p Value (550℃, 0.244 Ω·cm) 2This is attributed to the lattice distortion and increased oxygen vacancies caused by high-entropy BZCSYYbS doping, which lowers the activation energy for ion migration. Simultaneously, the enhanced BO bonds improve charge transfer efficiency, thereby increasing R0 and R... p Decrease.

[0052] Figure 7 This is a comparison of the conductivity and activation energy of the BZCSYYbS electrolyte fuel cell and the pure BZCY electrolyte fuel cell in this embodiment at 550-310℃. It can be seen that the BZCSYYbS electrolyte prepared in this embodiment can significantly improve the ionic conductivity and reduce the proton migration activation energy of the fuel cell. At 550℃, the ionic conductivity of the BZCY electrolyte battery is 0.216 S·cm. -1 The ionic conductivity of the BZCSYYbS electrolyte battery is 0.234 S·cm. -1 Within the temperature range of 550-400℃, the activation energy of BZCSYYbS is 0.255 eV, lower than that of BZCY (0.259 eV). In the lower temperature range of 400-310℃, the activation energy of BZCSYYbS is 0.812 eV, significantly better than that of BZCY (1.109 eV). This significant reduction in activation energy clearly demonstrates that the high-entropy design effectively lowers the ion migration barrier.

[0053] XPS analysis was used to evaluate the surface chemical composition and elemental valence states of BZCY and BZCSYYbS. Under the same testing conditions, Ce was obtained by peak fitting. 3+ Ce 4+ The changes in oxygen vacancy content and the relative content of oxygen vacancies were used to compare the impact of high-entropy design on surface defect chemistry. Figure 8 XPS full spectra of the BZCSYYbS sample are shown, with clearly visible characteristic peaks for Ba, Zr, Ce, Y, O, and C. Furthermore, signals for Ba, Zr, Ce, Sn, Y, Yb, and Sc were detected in the high-entropy BZCSYYbS, confirming the successful introduction of the target elements into the BZCY lattice. Quantitative surface chemical information was obtained through peak fitting of the fine spectra of O 1s and Ce 3d. Figure 8 As shown in b, the O1s spectrum can be fitted with peaks: namely O1 (lattice oxygen), O2 (defective oxygen from oxygen vacancies / hydroxyl groups), and O3 (adsorbed oxygen). The calculated relative contents of oxygen vacancies are listed in Table 3 and plotted on [the graph]. Figure 8 d. The results show that the BZCSYYbS electrolyte has a significantly higher oxygen vacancy concentration than the BZCY electrolyte, indicating that the high-entropy electrolyte design effectively introduces abundant proton transport active sites. Analysis of the Ce 3d spectrum ( Figure 8 c) Further revealed the stability of the valence state, and Ce was analyzed through peak fitting. 3+ With Ce 4+The characteristic peak of Ce. Calculated Ce 3+ / (Ce 3+ +Ce 4+ The ratio is as follows Figure 8 d is shown in Table 2. It is worth noting that Ce in high-entropy BZCSYYbS 4+ The higher proportion of oxygen vacancies in BZCY indicates that high-entropy design is beneficial for stabilizing the valence state of Ce. In doped BZCY, the increase in oxygen vacancy concentration is often accompanied by an increase in Ce. 4+ Severe reduction; while BZCSYYbS, through multi-principal synergistic effect, effectively inhibits Ce while introducing a higher concentration of oxygen vacancies. 4+ The reduction of Ce was attributed to the thermodynamic stabilizing effect of high configurational entropy (1.61 R) on the Ce valence state, the charge compensation buffering effect provided by local lattice distortion, and the synergistic regulation of Ce redox potential by multi-element doping.

[0054] Table 2 Different valence states (Ce) of BZCY and BZCSYYbS electrolytes 4+ Ce 3+ XPS peak area and percentage of valence state of each component.

[0055] Table 3. XPS peak areas of different oxygen species in BZCY and BZCSYYbS, and the ratio of the sum of peak areas attributed to oxygen vacancies and adsorbed oxygen to the peak area of ​​lattice oxygen.

[0056] Comparative Example 1: BaCeO3 matrix electrolyte (for performance comparison) BaCO3 and CeO2 were weighed according to a stoichiometric ratio of Ba:Ce = 1:1, with BaCO3 in excess by 5 mol%. The same ball milling, sintering, and secondary ball milling processes as in Example 1 were used, but the powder was sintered at 1300°C for 10 hours to obtain BaCeO3 electrolyte powder. The testing conditions were exactly the same as in Example 1.

[0057] The LT-SOFC device with Ni-Na was also prepared according to the method in Example 1. 0.15 Li 0.85 NCAF 0.10 |BaCeO3|Na 0.15 Li 0.85 NCAF 0.10 -Ni sandwich structure.

[0058] Under the same test conditions, such as Figure 9 As shown, the peak power density at 550℃ is 766 mW·cm³. -2 Power density at 350℃: 77 mW·cm³-2 The battery operated stably at 550°C for approximately 3 hours. Compared to Example 1, the battery prepared in this embodiment exhibited significantly reduced electrochemical performance and long-term stability at 520-350°C.

[0059] Comparative Example 2: Classic BZCY Electrolyte (for performance comparison) BaCO3, CeO2, ZrO2, and Y2O3 were weighed according to the stoichiometric ratio Ba:Ce:Zr:Y = 1:0.70:0.10:0.20, with BaCO3 in excess by 1.5 mol%. The same ball milling, sintering, and secondary ball milling processes as in Example 1 were used, but the powder was sintered at 1400°C for 10 hours to obtain BZCY electrolyte powder. The testing conditions were exactly the same as in Example 1.

[0060] The LT-SOFC device with Ni-Na was also prepared according to the method in Example 1. 0.15 Li 0.85 NCAF 0.10 |BZCY|Na 0.15 Li 0.85 NCAF 0.10 -Ni sandwich structure.

[0061] Under the same test conditions, such as Figure 10 As shown, the peak power density at 550℃ is 936 mW·cm³. -2 310℃ power density 23mW·cm -2 The battery prepared in this comparative example exhibited significantly reduced electrochemical performance and long-term stability at 520-310℃ compared to Example 1. The stable operation time at 550℃ was approximately 12 hours.

[0062] Comparative Example 3: Equimolar High-Entropy BZCSYYbS Electrolyte (High-Entropy Comparison) BaCO3, CeO2, ZrO2, SnO2, Y2O3, Yb2O3, and Sc2O3 were weighed according to the stoichiometric ratio Ba:Ce:Zr:Sn:Y:Yb:Sc = 1:(1 / 6):(1 / 6):(1 / 6):(1 / 6):(1 / 6):(1 / 6), with BaCO3 in excess by 1.5 mol%. The same ball milling, sintering, and secondary ball milling processes as in Example 1 were used. The test conditions were exactly the same as in Example 1.

[0063] The LT-SOFC device with Ni-Na was also prepared according to the method in Example 1. 0.15 Li 0.85 NCAF 0.10 |BZCSYYbS|Na 0.15 Li 0.85 NCAF 0.10-Ni sandwich structure.

[0064] Due to the low proportion of +4 valence elements (Ce, Zr, Sn), the average valence state at the B site decreases, the stability of the cubic phase structure declines, and the electrochemical performance is significantly lower than that of Example 1; the battery device even exhibits no power density at 310°C. While equimolar design can achieve a higher configuration entropy (1.79R), the functions of each element are not differentiated, and the low Ce content results in insufficient contribution to intrinsic conductivity. This indicates that a high configuration entropy is not necessarily better; optimizing the proportions of non-equimolar elements is key to achieving optimal ionic conductivity.

[0065] Comparative Example 4: Non-equimolar ratio BZCSYYbS electrolyte (Ce / Zr ratio interchangeable) BaCO3, CeO2, ZrO2, SnO2, Y2O3, Yb2O3, and Sc2O3 were weighed according to the stoichiometric ratio Ba:Ce:Zr:Sn:Y:Yb:Sc = 1:0.25:0.35:0.15:0.1:0.1:0.05, with BaCO3 in excess by 1.5 mol%. The same ball milling, pre-sintering, and sintering processes as in Example 1 were used. The test conditions were exactly the same as in Example 1.

[0066] The LT-SOFC device with Ni-Na was also prepared according to the method in Example 1. 0.15 Li 0.85 NCAF 0.10 |BZCSYYbS|Na 0.15 Li 0.85 NCAF 0.10 -Ni sandwich structure.

[0067] Ce 4+ (1.01 Å) radius greater than Zr 4+ (0.72 Å) When the Ce / Zr ratio changes from 0.35:0.25 to 0.25:0.35, the average ionic radius at the B site decreases. The tolerance factor of this comparison is about 0.930, which is significantly lower than that of Example 1, deviating from the stable range of the cubic phase. The stability of the cubic phase structure decreases, and the electrochemical performance is significantly lower than that of Example 1.

[0068] Comparative Example 5: Using the electrolyte from Example 1, LT-SOFC commonly uses LiNi 0.80 Co 0.15 Al 0.05 O2 (LNCA) electrode According to the stoichiometric ratio Na:Li:Ni:Co:Al:F = 1:0.80:0.15:0.05, raw materials including LiOH·H2O (≥98.0%, with an additional 5 mol% excess to compensate for lithium volatilization), NiO (Ni content 61%), Co3O4 (≥99.9%), and Al2O3 (≥99.99%) were weighed. The same ball milling, pre-sintering, and sintering processes as in Example 1 were used. The test conditions were exactly the same as in Example 1.

[0069] Similarly, the LT-SOFC device with a Ni-LNCA|BZCSYYbS|LNCA-Ni sandwich structure was prepared according to the method in Example 1.

[0070] Under the same test conditions, the power density of the battery in this comparative example decreased significantly between 400°C and 550°C. More importantly, the battery device exhibited no power density below 370°C and no durability at 550°C.

Claims

1. A non-equimolar high-entropy proton conductor electrolyte material, characterized in that, The electrolyte material has a chemical formula such as BaCe. 0.35 Zr 0.25 Sn 0.15 Y 0.10 Yb 0.10 Sc 0.05 O 3-δ As shown, δ represents the oxygen vacancy content, 0 < δ < 0.25; the tolerance factor of the electrolyte material is 0.967; the valence state content of Ce in the electrolyte material is Ce. 4+ / (Ce 3+ +Ce 4+ The content of the electrolyte material is 68.2%; the electrolyte material has a cubic perovskite structure. The preparation method of the electrolyte material includes the following steps: (1) Weigh out the Ba source, Ce source, Zr source, Sn source, Y source, Yb source and Sc source according to the stoichiometric ratio; (2) The weighed raw materials are ball-milled, mixed, and dried to obtain a mixed powder; (3) The mixed powder was pre-calcined at 900℃ for 6 h and then ground to obtain pre-calcined powder; (4) The pre-calcined powder was sintered at 1400℃ for 10 h and then ground to obtain the sintered powder. (5) The sintered powder is ball-milled and dried to obtain electrolyte powder.

2. The electrolyte material according to claim 1, characterized in that, In steps (2) and (5), the ball milling speed is 200~300 r / min and the time is 7~9 h.

3. The electrolyte material according to claim 1, characterized in that, In step (1), the Ba source is selected from BaCO3; the Ce source is selected from CeO2; the Zr source is selected from ZrO2; the Sn source is selected from SnO2; the Y source is selected from Y2O3; the Yb source is selected from Yb2O3; and the Sc source is selected from Sc2O3. Among these, the Ba source is used in excess of 3-8 mol compared to the stoichiometric amount.

4. The application of the electrolyte material according to any one of claims 1-3 in a solid oxide fuel cell.

5. A solid oxide fuel cell, characterized in that, The electrolyte material comprising the non-equimolar high-entropy proton conductor as described in any one of claims 1-3.

6. The solid oxide fuel cell according to claim 5, characterized in that, The anode and cathode materials of the solid oxide fuel cell are both Na. 0.15 Li 0.85 Ni 0.80 Co 0.15 Al 0.05 F 0.10 O 1.9-δ , 0 < δ < 0.25.

Citation Information

Patent Citations

  • High-entropy perovskite electrolyte and preparation method and application thereof

    CN116895811A